Microstructural degradation of polycrystalline superalloys from oxidized carbides and implications on crack initiation. (1st April 2018) - Kontis, Paraskevas; Collins, David M.; Wilkinson, Angus J.; Reed, Roger C.; Raabe, Dierk; Gault, Baptiste
Abstract: Surface connected carbides in a polycrystalline superalloy oxidized at 750 °C in air were studied as potential crack initiation sites. Lattice rotations measured in the γ/γ′ grains using high-resolution electron backscatter diffraction enabled investigation of the plastic deformation induced solely by the oxidation of carbides. Dislocations were found to enhance γ′ precipitate dissolution kinetics, resulting in soft recrystallized regions in the vicinity of the oxidized carbide with substantial compositional variation compared to the original γ/γ′ microstructure. Ramifications of such deleterious oxidized carbides alongside soft recrystallized regions on the crack initiation life in superalloys are discussed. Graphical abstract: Image 1